Retracted - Raza, Ali; Sahito, Abdul Aziz; Khokhar, Riaz Hussain; Memon, Waseem Raja; Malik, Ali Kashif; Hussain, Khawar (Indus Journal of Bioscience Research, 2025)
Introduction: Acute upper gastrointestinal bleeding (AUGIB) is a serious complication of liver cirrhosis with significant mortality. Early risk stratification is crucial. This study aimed to evaluate the diagnostic accuracy of the Albumin-Bilirubin (ALBI) score in predicting in-hospital mortality among cirrhotic patients presenting with AUGIB. Methodology: A descriptive longitudinal study was conducted on 180 patients with liver cirrhosis and AUGIB. The ALBI score was calculated using serum albumin and bilirubin levels. Receiver operating characteristic (ROC) analysis was performed to assess the predictive value of the ALBI score, with stratification based on gender, age, diabetes, hypertension, cirrhosis duration, hospital stay, and Child-Pugh class. Results: The ALBI score showed good overall predictive accuracy with an AUC of 0.816 (95% CI: 0.74–0.89, p=0.001). The optimal cut-off value was -1.50, yielding 90.9% sensitivity and 66.7% specificity. Stratified analysis showed the best performance in females (AUC 0.907), patients aged ≤50 years (AUC 0.850), and diabetics (AUC 0.830). High sensitivity was maintained across most subgroups. Conclusion: This study demonstrates the Albumin-Bilirubin (ALBI) score as a valuable tool for predicting in-hospital mortality in cirrhotic patients with acute upper gastrointestinal bleeding (AUGIB). Unlike traditional scores, ALBI is objective, simple, and based solely on albumin and bilirubin levels. In our cohort of 180 patients, it showed strong predictive performance (AUC 0.816), with a cut-off of -1.5 yielding 90.9% sensitivity and 66.7% specificity. It performed particularly well in females, younger patients, and those with shorter cirrhosis duration. Given the high mortality rate (18.3%), early risk stratification using ALBI may improve outcomes. Further multicenter studies are needed for validation.